The stress field due to an interfacial edge dislocation in a multi-layered medium. (15th October 2015) - Khanna, Aditya; Kotousov, Andrei
Abstract: We consider the problem of a multi-layered medium composed of an arbitrary number of perfectly bonded isotropic layers, with different thicknesses and elastic properties, when an edge dislocation of arbitrary orientation is present along one of the interfaces. A new effective solution is obtained for the complete stress and displacement fields induced by the interfacial edge dislocation in the multi-layered medium. The solution for the stress field due to the interfacial edge dislocation can be utilized to formulate governing equations for multiple interacting cracks in a multi-layered medium, with no restriction on the crack orientation, position and loading. The edge dislocation solution is validated directly by comparing it to available edge dislocation solutions and indirectly by revisiting some previously examined interfacial crack problems.